Caping Hat Ethnomathematics: Literature Review and Relevance in Mathematics Learning Cone Material - Sariyanti, Eka; Awaliyah, Ilka Nur; Syafitri, Kintan Salsabila Hasria; Noviani, Evi (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
Mathematics is still a problem for students and teachers today, because it is abstract, difficult to understand and requires accuracy in its implementation. Mathematics is also an object or lesson that is considered difficult to learn according to society. Apart from that, there are those who show the perspective that mathematics is not related to what they experience in their lives. This is because the abstract nature of mathematics and the way teachers present the material, which only provides definitions, formulas, example questions and practice questions that are not contextual, has become a long tradition and is still being applied. The current problem is that it only focuses on books and teachers so that it does not provide a meaningful understanding effect for students. Reforming mathematics learning, which was initially only an abstract concept and only a shadow, can certainly be integrated into their daily lives. The form of integrating mathematics learning can use a local culture-based approach that is close to students. One of them is using a hat object. Physically, hats are known to have a structure similar to a cone. Because the visual is similar to a cone, the researchers looked at it from the perspective of the work through one application, namely Geogebra. Learning with the Geogebra application can be used as an alternative for teaching mathematical objects that are abstract and difficult to teach. Therefore, Geogebra can help in visualizing curved sided shapes, one of which is a cone shape. The aim of this research is to explore the mathematics involved in caping using geogebra media. After conducting exploration, the researcher studied mathematical concepts obtained from mathematics learning materials, especially the shape of caps. Researchers use qualitative methods with an ethnographic approach because they are considered very relevant to cultural studies studies. The research results show that hats contain mathematical elements, especially geometric concepts, which can be integrated through Geogebra learning media.